Rattus tanezumi Temminck 1844 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Rattus tanezumi Temminck 1844 Rattus tanezumi Temminck 1844, in: Siebold, Temminck, and Schlegel, Fauna Japonica, Arnz et Socii, Lugduni Batavorum: 51. Type Locality: Japan, possibly from near Nagasaki on Kyushu Isl (see Jones and Johnson, 1965). Vernacular Names: Oriental House Rat. Synonyms: Rattus alangensis Chasen 1937; Rattus amboinensis Laurie and Hill 1954; Rattus argyraceus Sody 1941; Rattus auroreus Sody 1941; Rattus barussanoides Sody 1941; Rattus benguetensis Hollister 1913; Rattus bhotia Hinton 1918; Rattus brevicaudus Kuroda 1952; Rattus brevicaudus Chakraborty 1975; Rattus brunneus (Hodgson 1845); Rattus brunneusculus (Hodgson 1845); Rattus bullocki Roonwal 1948; Rattus canna (Swinhoe 1871); Rattus coloratus (Hollister 1913); Rattus dammermani Thomas 1921; Rattus dentatus (Miller 1913); Rattus diardii (Jentink 1880); Rattus exsul (Miller 1913); Rattus flavipectus (Milne-Edwards 1872); Rattus fortunatus (Miller 1913); Rattus gangutrianus Hinton 1919; Rattus germaini (Milne-Edwards 1872); Rattus griseiventer (Bonhote 1903); Rattus insulanus (Miller 1913); Rattus kadanus Chasen 1937; Rattus kelleri (Mearns 1905); Rattus khyensis Hinton 1919; Rattus kurokuma Kuroda 1953; Rattus kramensis Kloss 1919; Rattus lalolis Tate and Archbold 1935; Rattus lanensis Kloss 1919; Rattus lontaris Chasen 1937; Rattus macmillani Hinton 1919; Rattus makassarius Sody 1941; Rattus makensis Kloss 1916; Rattus mansorius Johnson 1962; Rattus masaretes Sody 1937; Rattus mesanis Kloss 1919; Rattus mindanensis (Mearns 1905); Rattus moheius Chasen 1937; Rattus molliculus Robinson and Kloss 1922; Rattus moluccarius Sody 1933; Rattus neglectus (Jentink 1880); Rattus nemoralis (Blyth 1851); Rattus obiensis Sody 1941; Rattus ouangthomae (Milne-Edwards 1872); Rattus palelae Miller and Hollister 1921; Rattus palembang Tate and Archbold 1935; Rattus panjius Chasen 1937; Rattus pannellus (Miller 1913); Rattus pannosus (Miller 1900); Rattus pelengensis Sody 1941; Rattus pipidonis Chasen 1937; Rattus poenitentiarii (Kloss 1915); Rattus ...